Partisipasi Anggota Kelompok Wanita Tani (KWT) Dalam Kegiatan Pekarangan Pangan Lestari Mendukung Ketahanan Pangan Rumah Tangga Di Kabupaten Gunungkidul DI Yogyakarta - Dian Pratama; Roso Witjaksono; Alia Bihrajihant Raya (Universitas Gadjah Mada, 2022)
ABSTRACTThe conversion of agricultural land that was still happening caused a decrease in land for food production. Decrease in food production could reduce food availability so that it became a threat to food resilience. The Ministry of Agriculture in 2020 launched the Sustainable Food Garden or Pekarangan Pangan Lestari (P2L) activity which aimed to increased availability, accessibility, and utilization of food. The success of P2L activities was determined by the participation of farmer women’s group members or Kelompok Wanita Tani (KWT) members in these activities. The objectives of the study were to: (1) Describing the participation of farmer women’s group members in P2L activities, and (2) Describing the effect of farmer women’s group members participation in P2L activities on household food resilience.This research was carried out with 6 KWT samples of beneficiaries of P2L activities in 2020 in Gunungkidul Regency which were taken by stratified cluster sampling. Primary data collection was done by direct interviews using a questionnaire to 138 respondents from KWT members taken by random sampling from 6 KWT samples. Data analysis had been done by using descriptive statistic and simple linear regression.The results showed that KWT members often and very often participated of attendance, but KWT members never and rarely participated of money and new ideas in P2L activities. The results of simple linear regression analysis showed that the participation of KWT members had a significant effect on household food resilience, namely the more often the participation of KWT members in P2L activities, the household food resilience of KWT members increases.